KELASE LEARNING METHODS TO IMPROVE LEARNING OUTCOMES FLIPPED CLASSROOM - Tangkin Mangesa, Riana (Letters in Information Technology Education (LITE), 2018)
Various teaching methods applied through information and communication technology (ICT) in learning becomes one important thing to improve learning outcomes. The application of ICT in learning to be one of the important things for the improvement of the quality of learning. Various learning methods are also implemented by integrating ICT in its implementation. One of the methods which used in this research is flipped classroom. Flipped classroom model in this research uses the development of video and audio media and e-learning platform kelase as online media that can be used to support flipped classroom model study. This study aims to improve the quality of student learning outcomes. The method which used in this research is a classroom action research methods. The results showed an increase in learning, cognitive domain results, the minimum cycle I and II increasedIn the affective domain the learning results of cycles I and II show excellent results.Student perceptions of applying classes